SYSTEM OF PUBLIC-PRIVATE PARTNERSHIP FINANCING OF INFRASTRUCTURE PROJECTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the system of public-private partnership financing of infrastructure projects. In addition, measures to expand the use of publicprivate partnership in the country, the adoption of legal acts, the problems associated with the effective implementation of public-private partnership projects were studied.